Evidence of pair production of longitudinally polarised vector bosons and study of CP properties in ZZ → 4ℓ events with the ATLAS detector at s $$ \sqrt{s} $$ = 13 TeV. (Tufts University. Tisch Library., 2024)
Keywords : Electroweak Interaction, Hadron-Hadron Scattering, Vector Boson Production.; Springer Open.